Pengaruh Model Pembelajaran Kooperatif Tipe Two Stay Two Stray Terhadap Keaktifan Belajar SKI Siswa di MAN 6 Pasaman Barat - Sri Mulyati; Charles Charles; Arman Husni; Al Baihaqi Anas (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2023)
This research was conducted at MAN 6 West Pasaman which was motivated by the lack of active learning of students in SKI subjects, where in the learning process the teacher only used conventional learning models. This makes students not interested in learning, they feel bored so that learning objectives have not been achieved optimally. This study aims to determine whether there is an influence of the Two Stay Two Stray cooperative learning model on student learning activity. This study uses a quantitative experimental approach with the type of quasi-experimental research (quasi-experimental). The data collection technique uses questionnaires and documentation. Data analysis starts from the normality test, homogeneity test and hypothesis testing. Based on the results of the analysis and discussion of the research data, the results of hypothesis testing were obtained using the Independent Sample Test, so the parametric statistical test results can be seen if sig (2-tailed) = 0.000 ≤0.05 then it is rejected and accepted. So that it can be concluded that there is an influence of the two stay two stray cooperative learning model on student learning activity at MAN 6 West Pasaman.